Delayed Gastric Emptying Associates With Diabetic Complications in Diabetic Patients With Symptoms of Gastroparesis. (November 2019) - Parkman, Henry P.; Wilson, Laura A.; Farrugia, Gianrico; Koch, Kenneth L.; Hasler, William L.; Nguyen, Linda A.; Abell, Thomas L.; Snape, William; Clarke, John; Kuo, Braden; McCallum, Richard W.; Sarosiek, Irene; et al.
Abstract : OBJECTIVES: Diabetic gastroparesis (Gp) occurs more often in type 1 diabetes mellitus (T1DM) than in type 2 diabetes mellitus (T2DM). Other diabetic end-organ complications include peripheral neuropathy, nephropathy, and retinopathy (together termed triopathy ). This study determines the prevalence of diabetic complications (retinopathy, nephropathy, and peripheral neuropathy) in diabetic patients with symptoms of Gp, assessing the differences between T1DM and T2DM and delayed and normal gastric emptying (GE). METHODS: Diabetic patients with symptoms of Gp underwent history and physical examination, GE scintigraphy, electrogastrography with water load, autonomic function testing, and questionnaires assessing symptoms and peripheral neuropathy. RESULTS: One hundred thirty-three diabetic patients with symptoms of Gp were studied: 59 with T1DM and 74 with T2DM and 103 with delayed GE and 30 without delayed GE. The presence of retinopathy (37% vs 24%; P = 0.13), nephropathy (19% vs 11%; P = 0.22), and peripheral neuropathy (53% vs 39%; P = 0.16) was not significantly higher in T1DM than in T2DM; however, triopathies (all 3 complications together) were seen in 10% of T1DM and 3% of T2DM ( P = 0.04). Diabetic patients with delayed GE had increased prevalence of retinopathy (36% vs 10%; P = 0.006) and number of diabetic complications (1.0 vs 0.5; P = 0.009); however, 39% of diabetic patients with delayed GE did not have any diabetic complications. DISCUSSION: In diabetic patients with symptoms of Gp, delayed GE was associated with the presence of retinopathy and the total number of diabetic complications. Only 10% of patients with T1DM and 3% of those with T2DM had triopathy of complications, and 39% of diabetic patients with Gp did not have any diabetic complications. Thus, the presence of diabetic complications should raise awareness for Gp in either T1DM or T2DM; however, diabetic Gp frequently occurs without other diabetic complications.